Farm2Fork Strategy: An Econometric Analysis of The Gini Index in Relation with The Vulnerable Workforce and Workforce Involved in Agricultural Activities - Adina A. NEAMTU (Communications of International Proceedings, 2022)
The Green Deal is the European Union's plan to recover from the sanitary and economic crisis by 2050. Farm2Fork's represents the heart of this plan. Transforming food chains and agricultural sector raises a series of challenges. Increased hunger, malnutrition and economic inequality are just some of them. This paper aims to conduct an analysis based on an econometric model of bifactorial linear regression. Through this analysis, the Gini index can be estimated - as a dependent variable in respect with to two other variables: the vulnerable employment rate and the employment rate in agriculture. The database has an annual frequency, containing values registered between 2000 and 2019 for Romania. The conclusions are at least interesting: an increase in labor force present in agricultural activities will result in a smaller Gini Index, hence a more equalitarian society. It seems agriculture could represent Romania`s Achilles’s heel.
Keywords: Green Deal; Farm2Fork; multiple regression model; agriculture; labor force